Commitment and the Organization: The Organization Man Revisited - Randall, Donna M. (Academy of Management Review, 1987)
The potential positive and negative consequences of varying levels of commitment both for employees and for the organization are discussed. It is argued that high levels of commitment to the organization may have severe negative consequences for individuals within the organization and for organizations themselves.